Critical points of performance in repeated sprint: A kinematic approach - de Andrade, V. L. [UNESP]; Palucci Vieira, L. H. [UNESP]; Kalva-Filho, C. A. [UNESP]; Santiago, P. R.P. (Elsevier, 2021)
Purpose: The objectives of the present study were to analyze possible changes in biomechanical patterns during a repeated sprint protocol and identify the mechanical factors that could influence performance. Methods: Sixteen male athletes (22.1 ± 3.1 years old, 78.6 ± 22.9 kg and 186.1 ± 10.1 cm in height) participated in this study. Warm-up exercises were performed. Thereafter, the subjects carried out the Running Anaerobic Sprint Test (RAST), composed of six explosive effort sprints of 35 m separated by 10 s of passive recovery. During the protocol, performed on an official indoor court (rigid surface), two cameras recorded performance parameters (time) while twelve cameras (OptiTrack™ Natural Point Inc. - USA) adjusted to 120 Hz, monitored the 3-D running kinematics. Results: The time length of effort (+11.6%; P < 0.05) increased from the first (4.67 ± 0.39 s) to the sixth (5.28 ± 0.36 s) repetitions. Significant changes were identified in stride frequency, contact time, stride time, horizontal speed of core body mass (BCM), and angle of thigh at touchdown (−14.9%; 19.1%; 8.2%; 17.0%; −18.8%; P < 0.05). Correlations were found between common step variables (i.e., SF and TS) and complex variables of the ankle, hips, and center of mass (BCM) kinematics (i.e., φthighTD, φthighTO, STDzH, ωkneeTD, θankleTD, and θankleTO) with the minimum Time (4.43 ± 0.37 s) and mean Time (4.91 ± 0.23 s) in the RAST. Conclusion: We can conclude that RAST performed on-court modify the mechanics of running and both, common and advanced kinematic measures such as derived from ankle, hips, and BCM motion are mechanical outputs linked with performance in this repeated sprint model.
Points critiques de performance sur sprint repété: une approache cinematique
Keywords: 3-D Kinematics; Fatigue; Running; Team sports